Transformasi Nelayan di Pesisir Kepulauan Bengkalis (Studi Tentang Pergerseran Pola Interaksi Sosial, Agama, Alat Penangkapan, dan Perubahan Ekosistem) - Hurmain Humain; Puriana Puriana (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Development paradigm shift toward people-centered development (people centered development) who appreciate and consider initiatives and local differences. Therefore, local communities should be able to explore and develop the potential socio-economic as well as manage the diverse socio-economic potential in order to develop independently and sustainable community development through community based. The results of field studies show that global flows and empowerment programs that have been implemented are not able to assist fishing communities to increase their incomes so that the empowerment program that existed for only a program that spends money without a clear purpose. Fishing effort in Bengkalis has huge potential if it is able to manage the opportunities and strengths and to minimize weaknesses and threats coming from inside and outside the business. During this time, due to lack of knowledge about good management, the management of fishing activities of daily routine that must be converted into how to develop it into a bigger business because its potential is still quite large and underutilized.